2021
DOI: 10.3390/e23080939
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Transfer Entropy Methods for the Study of Linear and Nonlinear Cardio-Respiratory Interactions

Abstract: Transfer entropy (TE) has been used to identify and quantify interactions between physiological systems. Different methods exist to estimate TE, but there is no consensus about which one performs best in specific applications. In this study, five methods (linear, k-nearest neighbors, fixed-binning with ranking, kernel density estimation and adaptive partitioning) were compared. The comparison was made on three simulation models (linear, nonlinear and linear + nonlinear dynamics). From the simulations, it was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…As a result, only the linear interactions could be captured, thereby ignoring possible nonlinearities that could be strongly affected by the exposure. Therefore, future work should focus on the quantification of these possibly nonlinear interactions ( Rozo et al, 2021 ). Secondly, the interactions between the features were assumed to be constant throughout the 15 or 45 min after the exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, only the linear interactions could be captured, thereby ignoring possible nonlinearities that could be strongly affected by the exposure. Therefore, future work should focus on the quantification of these possibly nonlinear interactions ( Rozo et al, 2021 ). Secondly, the interactions between the features were assumed to be constant throughout the 15 or 45 min after the exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Faes et al (2015) applied GC to map directional interactions in brain-brain and brain-heart networks in different sleep states, exemplifying the added value of GC in neuroscience ( Porta & Faes, 2015 ; Seth et al, 2015 ). A study by Rozo et al (2021) demonstrated that different methods to quantify RSA, based on GC principles, captured the cardiorespiratory changes expected during different non-REM sleep stages. Interactions between respiration, blood pressure and heart rate have been found to be influenced by factors such as body position ( Mary et al, 2019 ) and deep versus normal breathing ( Mary et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Laplace distribution provides a better representation of physiological signal noise than Gaussian noise [15]. Following Rozo et al [16], b was set to four. Thus, a nonlinear interaction was generated from X to Y at time lag 2.…”
Section: Nonlinear Modelmentioning
confidence: 99%
“…Lee et al proposed the D-V partitioning method (DVP) by combining fixed-binning quantization and an adaptive partitioning algorithm [15]. Rozo et al demonstrated that DVP was the best method for identifying the different interactions among the five most commonly used methods for TE computation [16]. Based on the idea of symbolic processing in permutation entropy [17], the symbolization is also a commonly used method for quantization in nonlinear measurement [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the choice of the best method to estimate TE for each specific application is still an open problem. For instance, Rozo et al studied five different estimation methods, and the results suggest the adaptive partitioning method outperformed [ 31 ]. However, the literature emphasizes that for highly nonlinear and non-Gaussian data, for example, in our case of cryptocurrency data, it is better to approach causality using the TE information method instead of the traditional Granger causality test [ 32 ].…”
Section: Introductionmentioning
confidence: 99%